2015
DOI: 10.1111/imm.12431
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of T‐bet expression in Mart‐127–35‐specific T‐cell‐receptor‐engineered human CD4+ CD25 and CD8+ T cells attenuates effector function

Abstract: SummaryGene transfer to create tumour epitope-specific cytolytic T cells for adoptive immunotherapy of cancer remains an area of active inquiry. When the Mart-1 27-35 -specific DMF5 T-cell receptor (TCR) is transferred into peripheral human CD4 + T cells, the reprogrammed cells exhibit a T helper type 1 (Th1) phenotype with significant multifactorial effector capabilities. The T-bet transcription factor plays an important role in determination of the Th1 differentiation pathway. To gain a deeper understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 55 publications
(247 reference statements)
2
7
0
Order By: Relevance
“…In our previous reports we have shown that when CTL precursors with specificity for a self but tumor-associated epitope are optimally stimulated, tTreg are not much of an impediment but iTreg or pTreg are [9][10][11][12]. Our previous results also indicated that the freshly isolated Treg cells consist of a heterogeneous group of CD4+ T cells (both tTreg and pTreg) [13].…”
Section: Research Articlementioning
confidence: 94%
See 3 more Smart Citations
“…In our previous reports we have shown that when CTL precursors with specificity for a self but tumor-associated epitope are optimally stimulated, tTreg are not much of an impediment but iTreg or pTreg are [9][10][11][12]. Our previous results also indicated that the freshly isolated Treg cells consist of a heterogeneous group of CD4+ T cells (both tTreg and pTreg) [13].…”
Section: Research Articlementioning
confidence: 94%
“…If available and permitted by the pathologists, surgically removed tumor tissues were also obtained. The details of the collection of samples and cell preparation have been described [9,10].…”
Section: Donorsmentioning
confidence: 99%
See 2 more Smart Citations
“…CD8 cells were capable of IFN-γ production, and no difference in the quantity of cytokine-producing cells was observed between groups ( Figure 1C). CD4 cells engineered to express the MHC class Irestricted F5 TCR have been previously described to exhibit a Th1 phenotype with increased IFN-γ production (33). CD4 cells expressing either F5 or F5/hdCK3mut produced equivalent IFN-γ when stimulated by PMA/ionomycin ( Supplemental Figure 1; supplemental material available online with this article; doi:10.1172/JCI77326DS1).…”
Section: Expression Of Hdck3mut Does Not Affect T Cell Function In VImentioning
confidence: 99%